2017
DOI: 10.1021/acs.inorgchem.7b00430
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Circularly Polarized Emission from Water-Soluble Eu(III)- and Tb(III)-Based Complexes: A Structural and Spectroscopic Study

Abstract: Water-soluble Eu(III) and Tb(III) complexes with N,N'-bis(2-pyridylmethyl)-trans-1,2-diaminocyclohexane-N,N'-diacetic acid (Hbpcd) have been synthesized and characterized in their racemic and enantiopure forms. The ligand has been designed to bind Ln(III) ions, providing a dissymmetric environment able to solicit strong chiroptical features while at the same time leaving a few coordination sites available for engaging further ancillary ligands. Potentiometric studies show that Ln(III) complexes have a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 61 publications
8
73
0
Order By: Relevance
“…As the paramagnetic Eu(III) and Tb(III) complexes are rather difficult to model computationally, the analogues of the diamagnetic Y(III) ion were studied. It has been shown that Y(III) complexes may serve as suitable models for the Eu(III) analogues, [33][34][35][36] consistently with the fact that its ionic radius differs from that of Eu(III) ion by about 0.05 Å [and less for Tb(III)]. Geometry optimizations of the [Y(L)(H2O)n] complexes were carried out at DFT level in vacuum using the B3LYP exchangecorrelation functional.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the paramagnetic Eu(III) and Tb(III) complexes are rather difficult to model computationally, the analogues of the diamagnetic Y(III) ion were studied. It has been shown that Y(III) complexes may serve as suitable models for the Eu(III) analogues, [33][34][35][36] consistently with the fact that its ionic radius differs from that of Eu(III) ion by about 0.05 Å [and less for Tb(III)]. Geometry optimizations of the [Y(L)(H2O)n] complexes were carried out at DFT level in vacuum using the B3LYP exchangecorrelation functional.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…39 This level of theory was previously demonstrated to provide correct geometries and thermochemical properties, maintaining the calculation feasible also with similar complex systems. 23,33 All final geometries were checked to be minima by vibrational analysis. Solvent effects were included by means of the PCM model.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…[15][16][17] However, chiral complexes of luminescent lanthanide ions have been exploited for their circularly polarized luminescence properties for decades [18][19][20] and that continues with many recent studies. [21][22][23][24][25] Circularly polarized luminescence (CPL) is the differential emission of left vs right circularly polarized light. The observables in CPL spectroscopy are the difference in emission intensity of left vs right circularly polarized light (I L -I R ) and sum of the emission intensity of left vs right circularly polarized light (I L + I R ), which is the total luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…27 Therefore, this mechanism depends on the type and arrangement of the ligands about the metal ion. 4,21,22,24,25,28,29 While Eu 3+ has been widely exploited for CPL applications, there are very few studies involving the CPL of Sm 3+ complexes. 18,27 Since 4f-4f transitions are magnetic dipole allowed (as long as ΔJ = 0,±1), the electric dipole transition mechanisms do not always dominate and can lead to large rotatory strengths compared with the dipole strength, resulting in a large g em (Equation 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation